Novel non-aggregated soluble metallophthalocyanines bearing carboxylic acid groups - Bayar, Serife; Dincer, Hatice A.; Ugur, Ahmet L. (TAYLOR & FRANCIS LTD, 2012)
Synthesis and characterization of zinc and cobalt phthalocyanines substituted with biphenylmethylpropionic acids, methyl-o-tolylpropionic acids, and methyl-p-tolylpropionic acids are described in this study. The new compounds have been characterized by elemental analyses, FT-IR, UV-Vis, MALDI-TOF, and H-1 NMR spectroscopy. All new compounds are soluble in THF, DMF, DMSO, and dilute sodium hydroxide solution. The influence of the carboxylic acid and bulky biphenyl, ortho-methylbenzyl and para-methylbenzyl groups on the spectroscopic properties has been investigated. UV-Vis experiments suggest that the tendency of phthalocyanines to aggregate in polar solvents is significantly reduced owing to the carboxylic acid groups and bulky peripheral substituents.
Keywords: Phthalocyanine; Carboxylic acid; Hydrolysis; Absorption; Aggregation; Polar solvent; EXCITED-STATE DYNAMICS; ZINC PHTHALOCYANINES; WATER; MACROCYCLES; PHOTOCATALYSTS; SUBSTITUENTS; OXIDATION; THERAPY; CELLS; TUMOR; Chemistry